Implications of qualitative trait diversity for future cowpea improvement and genetic resource conservation - Mekonnen, T.W.; Mekbib, Firew; Amsalu, B.; Gedil, Melaku A; Labuschagne, Maryke T. (Elsevier, 2022)
Understanding genetic diversity is indispensable for conserving and utilizing the genetic resources of orphan crops. Information on cowpea genetic resource collections, and its characterization and conservation in Ethiopia is limited. The objectives of this study were to determine the extent of genetic diversity within cowpea genotypes, assess the diversity patterns based on regions of origin, and identify regions for future cowpea collection and conservation. A total of 324 cowpea genotypes were evaluated using a 18 × 18 simple lattice design. Data on 22 qualitative traits were collected and subjected to the Shannon-Weaver diversity index (H') and multivariate analyses. A high level of diversity was evident amongst genotypes based on the frequency distribution of phenotypic traits. Individual phenotypic classes were not evenly distributed. The estimate of H' ranged from 0.45 (intermediate pod curvature) to 1.00 (growth habit). The highest (H'=0.77) and the lowest (H'=0.39) diversity values were obtained from the unknown category and the International Institute of Tropical Agriculture (IITA), respectively. Of the total variation, 82% was due to the populations within the regions of origin. Cluster analysis revealed five distinct groups. Seed colour and plant vigour contributed 84.9% of the variation in the first principal component between regions. In general, eye pattern, twining tendency, plant vigour, pod wall thickness, seed colour, testa texture, seed crowding, pod attachment to peduncle and immature pod pigmentation were the most effective traits for distinguishing amongst cowpea genotypes and could be used as selection criteria for improvement. This genetic diversity should be exploited by comprehensive cowpea variety development programs.